Perancangan Sistem Informasi Manajemen Gudang PT. X - Vini Aulia Zakiah Sodikin; Djamaludin; Reni Amaranti (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. PT. X is a textbook publishing and printing company that produces according to customer requests. In supporting these production activities, the company has a raw material warehouse. Currently, inventory data collection activities in the raw material warehouse are carried out on different physical documents, so that changes in the amount of material inventory cannot be known automatically when goods enter or leave. This causes the decision-making process in material replenishment to be hampered and ultimately affects the production process. An alternative that can be done in solving the problem is to design a company warehouse management information system that can provide accurate information on the availability of raw materials. The research stages follow the stages of system development with the Throwaway Prototyping Method which consists of four main stages, namely planning, analysis, design, and implementation. The results obtained are a warehouse management information system in the form of an application prototype which consists of the administration of receiving goods, the status of inventory in the warehouse and the administration of releasing goods from the warehouse. The prototype was built based on the needs and desires of the company. The results of the prototype test showed that information on the amount of raw material inventory can be known in real time so the prototype development can proceed to the design and implementation stages of the actual system. Abstrak. PT. X merupakan perusahan penerbitan dan percetakan buku pelajaran yang melakukan produksi sesuai dengan permintaan pelanggan. Dalam mendukung kegiatan produksi tersebut, perusahaan memiliki gudang bahan baku. Saat ini aktivitas pendataan persediaan di gudang bahan baku dilakukan pada dokumen fisik yang berbeda, sehingga perubahan jumlah persediaan material tidak memungkinkan diketahui secara otomatis saat barang masuk atau keluar. Hal ini menyebabkan proses pengambilan keputusan dalam pengisian kembali material menjadi terhambat dan pada akhirnya berpengaruh juga pada proses produksi. Alternatif yang dapat dilakukan dalam menyelesaikan masalah adalah merancang sistem informasi manajemen gudang perusahaan yang dapat memberikan informasi ketersediaan bahan baku secara akurat. Tahapan penelitian mengikuti tahapan-tahapan pengembangan sistem dengan Metode Throwaway Prototyping yang terdiri dari empat tahapan utama yaitu perencanaan, analisis, perancangan, dan implementasi. Hasil yang diperoleh yaitu sistem informasi manajemen gudang dalam bentuk prototype aplikasi yang didalamnya terdiri dari administrasi penerimaan barang, status persediaan barang di gudang dan administrasi pengeluaran barang dari gudang. Prototype dibangun berdasarkan pada kebutuhan dan keinginan dari pihak perusahaan. Hasil pengujian prototype didapatkan bahwa informasi jumlah persediaan bahan baku dapat diketahui secara real time sehingga pengembangan prototype dapat dilanjutkan ke tahap perancangan dan implementasi pada sistem yang sebenarnya.